Formation of Essential Ultrastructural Interface between Cultured Hippocampal Cells and Gold Mushroom-Shaped MEA- Toward “IN-CELL” Recordings from Vertebrate Neurons - Fendyur, Anna; Mazurski, Noa; Shappir, Joseph; Spira, Micha E. (Frontiers in Neuroengineering, 2011)
Using cultured Aplysia neurons we recently reported on the development of a novel approach in which an extracellular, noninvasive multi-electrode-array system provides multisite, attenuated, intracellular recordings of sub-threshold synaptic potentials and action potentials (APs), the so called “IN-CELL” recording configuration. Because of its noninvasive nature, the configuration can be used for long term semi intracellular electrophysiological monitoring of APs and synaptic potentials. Three principals converge to generate the IN-CELL configuration: (a) engulfment of approximately one micrometer size gold mushroom-shaped microelectrodes (gMµE) by the neurons, (b) formation of high seal resistance between the cell’s plasma membrane and the engulfed gMµE and (c), autonomous localized increased conductance of the membrane patch facing the gMµE. Using dissociated rat hippocampal cultures we report here that the necessary morphological and ultrastructural relationships to generate the IN-CELL recording configuration are formed between hippocampal cells and the gMµEs. Interestingly, even <1 µm thin branches expand and engulf the gMµE structures. Recordings of spontaneous electrical activity revealed fast ~2 ms, 0.04-0.75 mV positive monophasic action potentials (FPMP). We propose that the FPMP are attenuated APs generated by neurons that engulf gMµEs. Computer simulations of analog electrical circuits depicting the cell-gMµE configuration point out the parameters that should be altered to improve the neuron-gMµE electrical coupling.